Respuesta :
12.
y = kx
8 = -4k
so k = -2
y = -2x
y = -2 (7)
y = -14
13.
y = kx
15 = 6k
so k = 15/6 = 2.5
y = 2.5x
y = 2.5 (7)
y =17.5
14.
y = kx
3 = 9k
so k = 3/9 = 1/3
y = 1/3x
y = 1/3 (7)
y =7/3
15
y = kx
-4 = 4k
so k = -4/4 = -1
y = - x
y = - (7)
y = -7
16.
Yes. y varies directly with x
slope = (3+6)/(2+1) = 9/3 = 3
y = mx + b
-6= 3(-1) + b
b = -6 + 3 = -3
equation y = 3x -3
17.
Yes
slope = (2.5 - 7.5)/(-1+3) = -5/2 = -2.5
y = mx + b
7.5= -2.5(-3) + b
7.5 = 7.5 + b
so b = 0
equation
y = -2.5x
y = kx
8 = -4k
so k = -2
y = -2x
y = -2 (7)
y = -14
13.
y = kx
15 = 6k
so k = 15/6 = 2.5
y = 2.5x
y = 2.5 (7)
y =17.5
14.
y = kx
3 = 9k
so k = 3/9 = 1/3
y = 1/3x
y = 1/3 (7)
y =7/3
15
y = kx
-4 = 4k
so k = -4/4 = -1
y = - x
y = - (7)
y = -7
16.
Yes. y varies directly with x
slope = (3+6)/(2+1) = 9/3 = 3
y = mx + b
-6= 3(-1) + b
b = -6 + 3 = -3
equation y = 3x -3
17.
Yes
slope = (2.5 - 7.5)/(-1+3) = -5/2 = -2.5
y = mx + b
7.5= -2.5(-3) + b
7.5 = 7.5 + b
so b = 0
equation
y = -2.5x
12.
8 = k(-4)
k = -2
13.
15 = k(6)
k = 5/2
14.
3 = k(9)
k = 1/3
15.
-4 = k(4)
k = -1
16.
No, y does not vary directly with x
17.
Yes,
y = 5x/2
8 = k(-4)
k = -2
13.
15 = k(6)
k = 5/2
14.
3 = k(9)
k = 1/3
15.
-4 = k(4)
k = -1
16.
No, y does not vary directly with x
17.
Yes,
y = 5x/2